Rethinking American history in a global age - Bender, Thomas (University of California Press, 2002)
In rethinking and reframing the American national narrative in a wider context, the contributors to this volume ask questions about both nationalism and the discipline of history itself. The essays offer fresh ways of thinking about the traditional themes and periods of American history.